Digital Education Inequality and Youth Social Mobility in Indonesia’s 3T Regions - M. Badaruddin; Atikah; Finna Khairatun Muhardi; Haldi Jofanda (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
This study investigates how the lack of digital education access affects youth social mobility in Indonesia's underdeveloped (3T) regions. Using a quantitative analysis of BPS data, the research found significant infrastructural and educational gaps, with 65% of schools lacking internet and 35% lacking electricity. These deficits contribute to low educational attainment, a high 15% dropout rate, and limited opportunities for youth in these areas.Statistical findings confirmed a strong link between digital access and social mobility, with these factors accounting for 62% of the variation in outcomes. The study concludes that building digital infrastructure and improving digital literacy are essential for reducing inequality and fostering inclusive development. This research provides a critical foundation for creating targeted policies and suggests that future studies should explore the long-term impact of these interventions.